Autism Spectrum Disorder in Males with Sex Chromosome Aneuploidy: XXY/Klinefelter Syndrome, XYY, and XXYY. Issue 3 (April 2017) - Tartaglia, Nicole R.; Wilson, Rebecca; Miller, Judith S.; Rafalko, Jessica; Cordeiro, Lisa; Davis, Shanlee; Hessl, David; Ross, Judith
ABSTRACT: Objective: Neurodevelopmental concerns in males with sex chromosome aneuploidy (SCA) (XXY/Klinefelter syndrome, XYY, XXYY) include symptoms seen in autism spectrum disorder (ASD), such as language impairments and social difficulties. We aimed to: (1) evaluate ASD characteristics in research cohorts of SCA males under DSM-IV compared to DSM-5 criteria, and (2) analyze factors associated with ASD diagnoses in SCA. Methods: Evaluation of participants with XXY/KS (n=20), XYY (n=57) and XXYY (n=21) included medical history, cognitive/adaptive testing, Social Communication Questionnaire, Social Responsiveness Scale, Autism Diagnostic Observation Schedule, Autism Diagnostic Interview-Revised, and DSM ASD criteria. Clinical impressions of ASD diagnostic category using the ADOS and DSM-IV criteria were compared to ADOS-2 and DSM-5 criteria. T-tests compared cognitive, adaptive, SES and prenatal vs. postnatal diagnoses between ASD and no ASD groups. Results: ASD rates in these research cohorts were 10% in XXY/KS, 38% in XYY, and 52% in XXYY using ADOS-2/DSM-5, and were not statistically different compared to DSM-IV criteria. In XYY and XXYY, the ASD group had lower verbal IQ and adaptive functioning compared to those without ASD. Many children without ASD still showed some social difficulties. Conclusion: ASD rates in males with SCA are higher than reported for the general population. Males with Y chromosome aneuploidy (XYY and XXYY) were 4.8 times more likely to have a diagnosis of ASD than the XXY/KS group, and 20 times more likely than males in the general population (1 in 42 males, CDC 2010). ASD should be considered when evaluating social difficulties in SCA. Studies of SCA and Y-chromosome genes may provide insight into male predominance in idiopathic ASD.